2021
DOI: 10.1088/1361-6560/ac226c
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo-derived ionization chamber correction factors in therapeutic carbon ion beams

Abstract: The accuracy of electromagnetic transport in the GEANT4 Monte Carlo (MC) code was investigated for carbon ion beams and ionization chamber (IC)-specific beam quality correction factors were calculated. This work implemented a Fano cavity test for carbon ion beams in the 100–450 MeV/u energy range to assess the accuracy of the default electromagnetic physics parameters. The Urban and the Wentzel-VI multiple Coulomb scattering models were evaluated and the impact of maxStep, dRover, and final range parameters on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The mean excitation energies for water and air were set to 78 eV and 85.7 eV, respectively, adhering to the recommendation provided in ICRU 90 report 22 . Throughout this work, the production thresholds were set to 1 mm globally and 1 μm for a 2 × 2 × 2 cm 3 region around the scoring volume to fulfill the Spencer‐Attix condition of delta‐ray equilibrium 8,18,19 . In a previous study, using a production threshold larger than 5 μm was found to severely overestimate the beam quality correction factor 19 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean excitation energies for water and air were set to 78 eV and 85.7 eV, respectively, adhering to the recommendation provided in ICRU 90 report 22 . Throughout this work, the production thresholds were set to 1 mm globally and 1 μm for a 2 × 2 × 2 cm 3 region around the scoring volume to fulfill the Spencer‐Attix condition of delta‐ray equilibrium 8,18,19 . In a previous study, using a production threshold larger than 5 μm was found to severely overestimate the beam quality correction factor 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Tables 1 and 2 show the transport parameters used in this investigation for 60 Co and carbon ion beam simulations, respectively. The G4EMStandardOpt4 was previously found to pass the Fano cavity test for carbon ion beams within 0.3% and is considered to be highly accurate for both light and heavy charged particle transport 19,28,29 . The default stopping power tables for carbon ions in TOPAS use ICRU 73 values, which were overridden with the ICRU 90 data only for water and air, whereas, all other materials utilized the ICRU 73 data 21 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations